Grenada. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamerica de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Grenada during 2014 are identified, with respect to the needs and interests of the country, strengthening on topics such as export, finance, safety, business management, good agricultural practices, pollution management, organic farming, loss control, meat production, pest management, through organic pesticides and in the inclusion of women.